Strategi pemasaran bank syariah dalam menghadapi perkembangan industri keuangan di indonesia - Fachruddin, Mukhammad Hafidh (Maliki Interdisciplinary Journal, 2025)
The development of the financial industry in Indonesia presents new challenges and opportunities for Islamic banks. This journal aims to analyze effective marketing strategies for Islamic banks in facing increasingly competitive market dynamics. By using a SWOT analysis approach, this research identifies the strengths, weaknesses, opportunities and threats faced by Islamic banks. This article discusses marketing strategies for Islamic banks in facing the development of the financial industry in Indonesia. This research uses descriptive analytical techniques to identify various marketing strategies for Islamic banks in facing the development of the financial industry in Indonesia. The results of the analysis show that digitizing services, increasing public literacy, and strengthening collaboration networks are key strategies for increasing the competitiveness of Islamic banks. Apart from that, the importance of education and promotion of sharia products among the public is also emphasized to increase awareness and trust in sharia banking services. This research provides recommendations for Islamic bank managers to formulate marketing strategies that are innovative and responsive to changing consumer needs, so that they can contribute to the growth of the sharia-based financial sector in Indonesia.